2018
DOI: 10.1530/rep-18-0093
|View full text |Cite
|
Sign up to set email alerts
|

MEHP-induced rat testicular inflammation does not exacerbate germ cell apoptosis

Abstract: The testis is an organ that maintains an immune suppressive environment. We previously revealed that exposure of pre-pubertal rats to an acute dose of a well-described Sertoli cell toxicant, mono-(2-ethylhexyl) phthalate (MEHP), leads to an accumulation of CD11b+ immune cells in the testicular interstitial space that closely correlates with a robust incidence of germ cell (GC) apoptosis. Here, we test the hypothesis that the infiltrating immune cells contribute to GC apoptosis. Postnatal day 28 Fischer rats th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…Additionally, the expression pattern of tight-junction genes ( Ctnnb1 , Itgb1 , Sorbs1 ) suggested the potential involvement of the blood-testis barrier (BTB) in PTMφ response, consistent with previous observations of BTB disruption by MEHP exposure in peripubertal Fischer CDF344 rats ( Tiwary and Richburg, 2023 ). In prior studies, we also demonstrated that exposure to MEHP in peripubertal Fischer CDF344 rats resulted in a significant influx of immune cells when compared with adult rats ( Murphy et al , 2014 ; Voss et al , 2018 ). In line with those findings, the current study observed downregulation of several normal macrophage marker genes ( C1qa , C1qb , CX3CR1 ) and upregulation of the monocyte lineage gene marker CD68 , as well as upregulation of M2 macrophage-associated genes ( Arg1 , Mmp9 , Mafb ).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Additionally, the expression pattern of tight-junction genes ( Ctnnb1 , Itgb1 , Sorbs1 ) suggested the potential involvement of the blood-testis barrier (BTB) in PTMφ response, consistent with previous observations of BTB disruption by MEHP exposure in peripubertal Fischer CDF344 rats ( Tiwary and Richburg, 2023 ). In prior studies, we also demonstrated that exposure to MEHP in peripubertal Fischer CDF344 rats resulted in a significant influx of immune cells when compared with adult rats ( Murphy et al , 2014 ; Voss et al , 2018 ). In line with those findings, the current study observed downregulation of several normal macrophage marker genes ( C1qa , C1qb , CX3CR1 ) and upregulation of the monocyte lineage gene marker CD68 , as well as upregulation of M2 macrophage-associated genes ( Arg1 , Mmp9 , Mafb ).…”
Section: Discussionmentioning
confidence: 56%
“…Finally, sections were counterstained with DAPI and cover-slipped for microscopic observation. For Caspase 3 staining, the apoptotic index (AI) was calculated as the percentage of essentially round seminiferous tubules containing more than 3 Caspase 3-positive GCs in each cross section, as described in previous study ( Voss et al , 2018 ). An isotype-matched rabbit IgG antibody was used to evaluate the nonspecific binding of the primary antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes of testicular environment caused by abnormal expression of cytokines can induce excessive apoptosis [42,43]. Hence, we detected the expression of two key apoptosis proteins in testis, caspase-3 and caspase-9 acted an irreplaceable role in apoptosis [44].…”
Section: Discussionmentioning
confidence: 99%
“…After tissue injury, monocytes proliferate rapidly in the bone marrow and enter the circulation under the action of monocyte chemokine CCL2, which can reach the site of tissue injury within 1 h ( 23 ). Monocytes can also differentiate into dendritic cells or macrophages involved in the inflammatory response caused by testicular injury ( 22 , 24 ). Nemeth et al ( 25 ) examined the hematological parameters of rats after testicular ischemia-reperfusion, and observed that the white blood cell count and monocyte-granulocyte ratio increased significantly, and the monocyte-granulocyte ratio doubled on the first postoperative day.…”
Section: Discussionmentioning
confidence: 99%